Diagnostic value of ultrasound in the evaluation of the echostructures of the nodular formation of the thyroid gland using the classification system TI-RADS - A. F. Hummatov; S. A. Aliev; Kh. N. Shirinova; A. H. Abbasov (Клінічна хірургія, 2019)
Objective. Estimation of the ultrasonographic criteria efficacy in accordance to the TI-RADS system while determining the morphological structures of nodal thyroid affections.